Seashell-based bioceramics for advanced electrospun tissue scaffolds - Sema Nur Sahin; Erdi Bulus; Alper Tezcan; Muhammad Umar Farooq; Marwah Al-garash; Yesim Muge Sahin (The European Chemistry and Biotechnology Journal, 2025)
The demand for tissue scaffolds to support the repair, regeneration, and restoration of damaged tissues is rapidly growing. Scaffolds fabricated using the electrospinning technique are particularly significant in tissue engineering due to their ability to provide micro- to nano-scale porosity and a large surface area. This study focuses on developing tissue scaffolds with enhanced cell adhesion, biodegradability, and tensile strength by employing aqueous solutions of polyvinyl alcohol (PVA), a biocompatible and biodegradable synthetic polymer; gelatin (GEL), a natural polymer that offers binding sites conducive to cell adhesion and differentiation; and synthesized bioceramics, all integrated through the electrospinning process. Composite tissue scaffolds were engineered by incorporating 1% to 3% GEL into the PVA solution, followed by the addition of 1% bioceramics to the 1% GEL-enriched PVA. The composite formulation not only emulates the extracellular matrix as a biomimetic strategy but also goes beyond merely enhancing ossification. Comprehensive structural, morphological, mechanical, and thermal characterizations were conducted to analyze the properties of the scaffolds containing the synthesized bioceramics. The tensile strengths of the fabricated nanocomposites were determined to be 6.25 MPa for 10:0 (PVA:GEL), 7.45 MPa for 10:1 (PVA:GEL), 8.01 MPa for 10:3 (PVA:GEL), and 8.22 MPa for 10:1:1 (PVA:GEL:Bioceramics), respectively, indicating a progressive enhancement in mechanical properties with the incorporation of GEL and bioceramics. The results demonstrate the successful production of a potential biomaterial with ideal properties for tissue engineering applications. These composite scaffolds, providing a conducive environment for cell adhesion and exhibiting excellent mechanical properties, are anticipated to be suitable for dental applications as an intermediate layer which may support bone and connective tissue formation.